Civil society and state in Mexico: on the issue of the new forms of interaction - Iu. I. Vizgunova (Ибероамериканские тетради, 2015)
The paper deals with the relations of the civil society and state in México in the XXI-st century. The author analyzes the participation of the middle class, scientists and intellectuals in the structural reforms of the state institutions and their insert of the effective path of the realization of economic and social problems in the context of the possible Mexican development trajectory.